Blue-light induced breakdown of barrier function on human retinal epithelial cells is mediated by PKC-ζ over-activation and oxidative stress. (December 2019) - Ozkaya, Ege Kaan; Anderson, Graham; Dhillon, Baljean; Bagnaninchi, Pierre-Olivier
Abstract: We aimed to study the time course decrease of human retinal pigment epithelium (RPE) barrier function when exposed to blue light. To this end, we cultured ARPE-19 cells on Electrical Cell-substrate Impedance Sensing (ECIS) multi-well arrays. Using an ad hoc light emitting diode (LED) array illumination system together with a set of neutral density filters and a 3-dimensional (3D) printed filter holder, cells were exposed to a gradient of irradiances of blue-light with a measured peak at 468 nm. The electrical resistance between 4 kHz and 64 kHz was recorded during the exposure. Blue light exposure induced a dose-dependent decrease in the resistances at 4 kHz, however the time course resistance at 64 kHz did not show any decrease before t = 52 h. Quantification of the barrier function using mathematical model integrated in the ECIS software showed that blue-light exposure induced a dose-dependent decrease in the barrier function associated with tight junction formation (P < 0.05). This was confirmed by the immunostaining of the tight-junction associated structural protein, Zonula occludens-1 (ZO-1). The detection of reactive oxygen species by carboxy-H2DCFDA confirmed that the blue light induced dose-dependent decrease in the barrier function is mediated by oxidative stress. On a separate experiment, blue-light exposed ARPE-19 cells were treated with 100 nM Protein Kinase C zeta (PKC-ζ) pseudo substrate inhibitor to identify underlying pathway for blue-light induced damage on the barrier function. The treatment with 100 nM PKC-ζ pseudo substrate inhibitor induced faster recovery of the barrier function compared to no treatment. Altogether our results document that blue LED light exposure decreased RPE barrier function in-vitro in a dose-dependent manner, before any cell death occurred. This damage induced by blue-light on tight junctions is mediated by oxidative stress through PKC-ζ activation. The quantification of the healing effect observed by inhibition of PKC-ζ might lead to development of high throughput wound healing assays through ECIS in the future. Highlights: For the first time, the effect of blue light on the human cell line, is measured in real-time. Blue light decreases RPE barrier function in vitro, before any cell death occurs. Blue light exposure decreases RPE barrier function in a dose-dependent manner. The damage on tight junctions is mediated by oxidative stress through PKC-ζ activation.